2017
DOI: 10.1111/cas.13116
|View full text |Cite
|
Sign up to set email alerts
|

Mourning Dr. Alfred G. Knudson: the two‐hit hypothesis, tumor suppressor genes, and the tuberous sclerosis complex

Abstract: On July 10, 2016, Alfred G. Knudson, Jr., MD, PhD, a leader in cancer research, died at the age of 93 years. We deeply mourn his loss. Knudson's two‐hit hypothesis, published in 1971, has been fundamental for understanding tumor suppressor genes and familial tumor‐predisposing syndromes. To understand the molecular mechanism of two‐hit‐initiated tumorigenesis, Knudson used an animal model of a dominantly inherited tumor, the Eker rat. From the molecular identification of Tsc2 germline mutations, the Eker rat b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 79 publications
1
25
0
4
Order By: Relevance
“…(12) It can also be likened to the double-hit theory of many cancers. (24) It is also possible that in some cases this hypercoagulable condition by itself is enough to cause an embolic stroke. This may be correlated with elevated lab markers like D-Dimer or NLR ratio or presence of antiphospholipid antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…(12) It can also be likened to the double-hit theory of many cancers. (24) It is also possible that in some cases this hypercoagulable condition by itself is enough to cause an embolic stroke. This may be correlated with elevated lab markers like D-Dimer or NLR ratio or presence of antiphospholipid antibodies.…”
Section: Resultsmentioning
confidence: 99%
“…This second hit can be a genetic alteration, such as a deletion or somatic mutation, or can be an epigenetic alteration, such as hypermethylation. 28,29 In order to analyse the expression and methylation of MLH1, MSH2, MSH6 and PMS2 in EMPD comprehensively, we collected EMPD tumour samples from 57 unrelated EMPD patients and twenty normal skin tissues from the same patients. A high prevalence of hypermethylation in MSH2 gene in EMPD patients was detected by MSP (73.6%), followed by a consistent down-regulation of MSH2 protein expression (38.6%); this correlation was not identified in other MMR genes such as MLH1, MSH6 and PMS2.…”
Section: Discussionmentioning
confidence: 99%
“…The Eker rat strain was originally developed by R. Eker, a Norwegian pathologist. Dr Knudson later introduced the Eker rat to the USA for hereditary cancer studies and maintained the mutation by breeding the rats on a normal Long‐Evans strain background …”
Section: Research History and Resultsmentioning
confidence: 99%
“…Dr Knudson later introduced the Eker rat to the USA for hereditary cancer studies and maintained the mutation by breeding the rats on a normal Long-Evans strain background. 9 ) In the study of Eker rat renal carcinogenesis, Hino et al 6 found that the following four genes were highly involved in renal carcinogenesis: the third component of complement (C3) gene, the fosrelated antigen 1 (fra-1) gene, the calpactin I heavy-chain (annexin II) gene, and an unknown gene, which was later named the Erc gene. 8 In 2000, Yamashita et al 10 determined the full sequence of the Erc gene cDNA and its exon-intron structure; also, the Erc locus and the locus of the putative human homologue were mapped in the respective chromosomes by FISH.…”
Section: Brief History Of Research On the Erc/msln Gene And Its Promentioning
confidence: 99%